Pengaruh Pertumbuhan Ekonomi, Pengangguran, dan Kemiskinan terhadap Ketimpangan Pendapatan di Kalimantan Selatan - Verry Noval Ariadi; Muzdalifah (PPJP ULM, 2020)
This research was conducted to (1) Analyze the influence of finance,unemployment, and poverty partially on income inequality from 2010 to 2017. (2) Analyzethe effect of economic, unemployment, and poverty simultaneously on income inequality.(3) Analyzing the variables that are most dominant affecting income inequality.This research is quantitative. The data used in the study are secondary dataobtained through the Central Statistics Agency from districts/cities in South Kalimantan.The data analysis technique used is a quantitative analysis using panel data regressionanalysis with the Fixed Effect Model.This study's results are based on panel data regression analysis, which states theeconomy has no significant effect, significant unemployment, and poverty significantlyaffect income inequality in 13 districts/cities in South Kalimantan.